A Study of Effectiveness of Alfuzosin in Benign Prostatic Hyperplasia Patients During Prostate Awareness Campaign in Year 2006-2009 in Hospital Universiti Sains Malaysia (HUSM) - Hood, Goh Cheng (2013)
Benign prostate hyperplasia is a common benign disease in men after age of 50. Its prevalence is about 19 to 30 %. It is not a life threatening disease, but it does significantly reduce the quality of life in both men as well as their opposite partner. This condition affects the men in their daily routine activities, as well as their sexual lifestyle. The symptoms bothering the patients and disturbing their sleep are termed as Lower Urinary Tract Symptom (LUTS). These symptoms are recorded by using an objective scoring system, International Prostate Symptoms Score (IPSS) which was validated by World Health Organization (WHO). It contains seven questions and with scores of 0 to 5 for each question. Sum of all the scores will determine how severe the LUTS is. Although it is a bothersome disease, it is also a treatable disease. It can be treated either medically or surgically. The aim of this study is to find out how effective is the medication- Alfuzosin (Xatral) in this disease. It is a cross sectional study, the patients diagnosed as BPH from year 2006 to 2009 were recruited. A total of 307 who fulfilled the inclusion and exclusion criteria were included in the study. Patients who were recruited will be contacted by phone and appointment will be given, new set of IPSS and uroflow rate (Qmax) will be obtained and recorded during the interview. The data will be compared with the data prior to initiation of treatment and the result will be analyzed using SPSS version 19. The medical treatment outcome using Alfuzosin was compared with pre and post treatment using IPSS, Qmax. The data was analyzed using two means paired t-test and the results are significantly different in the two test groups. The means of IPSS improved significantly from 15.55 to 5.53 (p<0.001) and means Qmax from 11.74 to 14.51 (p <0.001). In the study group, 2% of the study population presented with acute urinary retention, which was resolved after starting on Alfuzosin; no others study patients presented with acute urinary retention during the period of study. The result also showed that serum prostate specific antigen levels decreased in patients on medical treatment from 4.69ng/ml to 3.33ng/ml (p=<0.001). v